Are we building preservice Teacher self-efficacy? A large-scale study examining Teacher education experiences. Issue 1 (1st January 2019) - Clark, Sarah; Newberry, Melissa
ABSTRACT: Teacher education programs are under great pressure to produce highly capable teachers. Teacher self-efficacy has been shown to correlate with teacher motivation and perseverance, yet little is known about how specific teacher education experiences predict teacher self-efficacy. Four sources contributing to teacher self-efficacy beliefs during teacher education programs include mastery experiences, vicarious experiences, verbal persuasion from teacher educators, and verbal persuasion from cooperating teachers. In this study, perceptions of these sources were examined to determine how well they correlate with and predict preservice teacher self-efficacy. Results showed all four variables were strong predictors of preservice teacher self-efficacy, but that these variables accounted for only 18% of the variance, suggesting additional sources need to be examined. Perceptions of training experiences were examined across nine programs (N = 783). Implications for teacher educators and mentor teachers are provided so as to find ways to strengthen preservice teacher self-efficacy.